Cultural revolution : exploring the what and how of remembering - Tay, Min (2019)
As the Cultural Revolution (CR) which took place in China between 1966-1976 unfolded in various degrees, individual recollections towards the event would not have been uniform. One thing for certain was that the Chinese Communist Party of China (CCP) has played an important role in shaping how the CR has been remembered. Hence, using the CR in China as an example, this paper seeks to uncover how the event has been remembered from alternative perspectives of people who experienced the event, in contrast to the state narrative. I argue that within state-sanctioned boundaries, there is a proliferation of materials remembering the Cultural Revolution beyond conventional mediums like printed publications – to include private museums and online websites – which collectively enriched the state narrative that promotes forgetting and negation of the CR, while facilitating bottom-up participation in the remembering from people who experienced the event. It is important to consider alternative memories from the bottom as part of the discourse since the CR impacted all of society. Intimate details and different perspectives offered could result in new interpretations and understanding of the CR as an event, allowing lessons to be drawn from the past to guide the future.